Tax Avoidance of Coal Mining Companies In Indonesia - Joko Susilo; Adli Adli (Publikasi Indonesia, 2023)
The objective of this research was to determine the impact of transfer pricing, yield management, thin capitalization, and hedging on tax avoidance. Tax avoidance refers to the legal framework for transactions that obtain tax benefits or relief by exploiting existing tax loopholes to minimize or avoid paying taxes owed. This research applied descriptive and quantitative methods. Population of this research consisted of coal mining companies listed on the Indonesian Stock Exchange between 2015 and 2019. Using targeted sampling techniques, the sample was drawn from 16 companies that met the research criteria. The statistical program Eviews12 was used to process the data. Transfer pricing, earning management, or hedging had no significant effect on tax avoidance. Simultaneously, thin capitalization had a significant effect on tax avoidance.